Skeletal Editing through Single-Atom Insertion and Transmutation: An Insight into a New Era of Synthetic Organic Chemistry - Patel, Chandresh K.; Kant, Kamal; Banerjee, Sourav; Kalita, Sangita; Atta, Ananta K.; Malakar, Chandi C. (Synthesis, 2024)
Considering the importance of heterocycles, significantly represented in medicinal chemistry and drug development, the single-atom insertion technique and transmutation strategy provide productive approaches towards complicated molecular structures through heterocycle diversification. It shows a potentially powerful approach for modifying complex substrates concisely and chemospecifically. Although skeletal editing applies to cyclic and acyclic compounds, this review focuses on the diversification of carbo- and heterocyclic compounds for synthesizing various medicinally important molecules via the single-atom insertion technique. The classification system is based on recent and critical historical methods of single-atom insertion as applied to the transmutation of aromatic rings.1 Introduction2 Skeletal Editing through Carbon-Atom Insertion2.1 Skeletal Editing of Indoles and Pyrroles Derivatives: Carbon-Atom Insertion into a C=C Bond2.2 Skeletal Editing of Pyrazole and Indazole Derivatives: Carbon-Atom Insertion into an N–N Bond2.3 Skeletal Editing of Pyrazole and Indazole Derivatives: Insertion of CF3 Group into Heteroarenes2.4 Skeletal Editing of Imidazole Derivatives: Carbon-Atom Insertion into C–N Bond2.5 Skeletal Editing through Atom-to-Atom Transmutation3 Skeletal Editing through N-Atom Insertion3.1 Nitrogen-Atom Insertion into Carbocycles3.2 Nitrogen-Atom Insertion into Heterocycles3.3 Carbon to Nitrogen Transmutation3.3 Molecular Editing through Isotopic Transmutation4 Conclusion
Keywords: atom insertion; atom exchange; skeletal editing; molecular editing; heterocycle diversification